2018
DOI: 10.3389/fimmu.2018.01975
|View full text |Cite
|
Sign up to set email alerts
|

High-Frequency, Functional HIV-Specific T-Follicular Helper and Regulatory Cells Are Present Within Germinal Centers in Children but Not Adults

Abstract: Broadly neutralizing antibodies (bnAbs) against HIV-1 are an effective means of preventing transmission. To better understand the mechanisms by which HIV-specific bnAbs naturally develop, we investigated blood and lymphoid tissue in pediatric infection, since potent bnAbs develop with greater frequency in children than adults. As in adults, the frequency of circulating effector T-follicular helper cells (TFH) in HIV infected, treatment naïve children correlates with neutralization breadth. However, major diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 77 publications
2
34
0
Order By: Relevance
“…CD4 ϩ Tfh cells are crucial in providing help to B cells in the germinal center (GC) to support antibody maturation (46) and have been shown to be associated with the development of bnAbs during SHIV infection (47), in HIV-infected adults (17), and, more recently, in HIV-infected children (33). A recent study of HIV-1 clade C vertically infected human children and adults demonstrated that frequencies of total Tfh (CXCR5 ϩ PD1 hi ) and HIV-specific (Gag/Env), IL-21-producing GC Tfh cells in oral lymphoid tissue were increased in older children receiving ART (age range, 6 to 10 years); however, it is unknown whether this is true in early life (33). Similarly, in our monkey model, we observed higher frequencies of total lymphoid Tfh and GC B cells in SHIV-infected infants than in adults at 12 wpi ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CD4 ϩ Tfh cells are crucial in providing help to B cells in the germinal center (GC) to support antibody maturation (46) and have been shown to be associated with the development of bnAbs during SHIV infection (47), in HIV-infected adults (17), and, more recently, in HIV-infected children (33). A recent study of HIV-1 clade C vertically infected human children and adults demonstrated that frequencies of total Tfh (CXCR5 ϩ PD1 hi ) and HIV-specific (Gag/Env), IL-21-producing GC Tfh cells in oral lymphoid tissue were increased in older children receiving ART (age range, 6 to 10 years); however, it is unknown whether this is true in early life (33). Similarly, in our monkey model, we observed higher frequencies of total lymphoid Tfh and GC B cells in SHIV-infected infants than in adults at 12 wpi ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The quality of these Tfh cell responses may not be optimal early in infection, as we observed that only about 50% of the monkeys in both age groups developed autologous virus neutralization responses by 12 wpi. Furthermore, the differences in Tfh and GC B cells may not be unique to SHIV infection, as the frequencies of lymphoid-resident Tfh cells are also higher in uninfected children than in uninfected adults (33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Frequencies of Tfh cells have been reported to be increased in HIV-infected children compared to adults (26). In order to investigate Tfh cell responses during the early phase of SHIV infection, we evaluated the proportions of CH505-specific (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…CD4+ T-follicular helper (Tfh) cells are crucial in providing help to B cells in the germinal center (GC) to support antibody maturation (34). A recent study of HIV-1 clade C-infected human children and adults demonstrated that frequencies of total Tfh (CXCR5+ PD1 hi ) and HIV-specific (Gag/Env), IL-21-producing GC-Tfh cells in oral lymphoid tissue were increased in older children receiving ART (age range: 6-10 years), however it is unknown whether this is true in early life (26). In our monkey model, we observed higher frequencies of total lymphoid Tfh cells and GC B cells in SHIV-infected infants compared to adults at 12 wpi (Fig.…”
Section: Discussionmentioning
confidence: 99%